Penggunaan Appsheet untuk Pencatatan Transaksi Sederhana pada Bisnis Kecil - Eric Waviandy (Ebiz Prima Nusa, 2022)
The development of increasingly sophisticated technology is an advantage for business development. Especially the new ones. With the rapid development of information technology, data transfer is also becoming faster. Information systems require the need to process daily transactions, support administrative activities and provide reports. The use of website-based applications can increase productivity in carrying out administrative activities such as recording transactions. Appsheet is an application that can be used to create transaction recording applications. Of course, with the addition of other applications such as Google Drive and Google Sheets. Some of these applications can be combined to create applications that can later be used to record transactions in small businesses such as the Independent Economic Movement (GEMI) conducted by residents of RT 04 RW 18, Cipageran Village, Cimahi City. Based on the research that has been done, it can be concluded that the application for recording transactions at GEMI can be designed in web form, using an Appsheet and using Google Sheets to store sales data. Based on the test results, it was found that this sales application can make it easier for the GEMI treasurer to process the transaction activities that occur, so that sales transaction data can be stored and managed properly in a Google Spreadsheet.